Addressing Work-Related Issues in Medical Rehabilitation: Revision of an Online Information Tool for Healthcare Professionals. (16th August 2016) - Lukasczik, Matthias; Wolf, Hans-Dieter; Gerlich, Christian; Küffner, Roland; Vogel, Heiner; Neuderth, Silke
Abstract : Background. Medical rehabilitation increasingly considers occupational issues as determinants of health and work ability. Information on work-related rehabilitation concepts should therefore be made available to healthcare professionals. Objective. To revise a website providing healthcare professionals in medical rehabilitation facilities with information on work-related concepts in terms of updating existing information and including new topics, based on recommendations from implementation research. Method. The modification process included a questionnaire survey of medical rehabilitation centers (n = 28 ); two workshops with experts from rehabilitation centers, health payers, and research institutions (n = 14 ); the selection of new topics and revision of existing text modules based on expert consensus; and an update of good practice descriptions of work-related measures. Results. Health payers' requirements, workplace descriptions, and practical implementation aids were added as new topics. The database of good practice examples was extended to 63 descriptions. Information on introductory concepts was rewritten and supplemented by current data. Diagnostic tools were updated by including additional assessments. Conclusions. Recommendations from implementation research such as assessing user needs and including expert knowledge may serve as a useful starting point for the dissemination of information on work-related medical rehabilitation into practice. Web-based information tools such as the website presented here can be quickly adapted to current evidence and changes in medicolegal regulations.